Expressão de microRNAs envolvidos com o crescimento muscular do pacu (Piaractus mesopotamicus): análises in vivo e in vitro - Duran, Bruno Oliveira da Silva [UNESP] (2015)
Pacu (Piaractus mesopotamicus) is a Brazilian fish with high economic interest for pisciculture due to features such as rusticity and fast growth. Postnatal growth of skeletal muscle in fish occurs by hyperplasia and/or hypertrophy, processes that are dependent on the proliferation and differentiation of myoblasts. A class of small noncoding RNAs, known as microRNAs (miRNAs), represses the expression of target mRNAs, and many studies demonstrate that miR-1, miR-133, miR-206 and miR-499 regulate different processes in skeletal muscle through the mRNA silencing of HDAC4, SRF, Pax7 and Sox6, respectively. The aim of our work was to evaluate the expression of miRNAs and their putative target mRNAs in fastand slow-twitch skeletal muscle of pacu during growth. Our results revealed an inverse correlation between the expression of miRNAs and their target mRNAs, and there was evidence that miR-1, miR-133 and miR-206 may regulate the proliferation and differentiation of myoblasts. On the other hand, miR-499 was highly expressed in slow-twitch muscle, which suggests its involvement in the specification and maintenance of the slow phenotype in muscle fibres. miRNA expression exhibited variations between different development stages and between distinct muscle twitch phenotypes. This work provided the first identification of miRNA expression profiles related to skeletal muscle in pacu and suggests an important role of these molecules in this tissue